Effect of amoxicillin-clavulanate and cephradine on the fecal flora of healthy volunteers not exposed to a hospital environment. - Brumfitt, W (1986)
A 7-day course of either cephradine or amoxicillin-clavulanate treatment caused no significant change in fecal flora composition, except that staphylococci were virtually eliminated in both groups. Some amoxicillin-resistant coliforms were isolated after treatment in both groups, but cephradine- or amoxicillin-clavulanate-resistant coliforms were rarely isolated.